NARASI JANNAH DALAM ALQURAN PERSPEKTIF LINGUISTIK BEHAVIORISME - Ubaidillah Ubaidillah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This study aims to explain about the contextualization of the meaning of the Qur'an so that Muslims do not fall into textual understanding even away from the truth. Using Bloomfield's theory of behaviorism linguistics, this research will add to the meaning of the Qur'an's linguistic meaning, especially those related to the description of paradise in the Qur'an which was of great interest to the Arab community at that time, so that many of them converted to Islam. After analyzing the Qur'anic verses describing the state of paradise and its pleasures, the researchers found three major stimuli related to the state of Arab society that gave rise to linguistic responses in the form of descriptions of paradise: geography, agricultural products and plantations, socio-cultural conditions of society.